2019
DOI: 10.1002/jhbp.673
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative serum albumin is associated with intra‐abdominal infection following major hepatectomy

Abstract: Background Major hepatectomy is a complex surgical procedure with high morbidity. Intra-abdominal infection (IAI) is common following hepatectomy and affects treatment outcomes. This study was performed to investigate perioperative factors and determine whether the preoperative serum albumin level is associated with IAI following major hepatectomy. Methods From January 2008 to December 2018, 268 patients underwent major hepatectomy. We retrospectively analyzed demographic data and preoperative and perioperativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…It was found that patients who have intraabdominal infection have significantly longer operative time than those in a non-intraabdominal infection group. 28 This is consistent with Chacon et al, who studied the effect of operative duration and infectious complications and mortality in a large population of patients who underwent hepatectomy. 30 It was found that an operative time greater than 3 h significantly increased mortality, with a considerable peak at 8 h. Furthermore, as the 30-day mortality rate increased in accordance with the operative time, it was concluded that operative time is associated with a linear increase of risk of mortality and infectious complications following hepatectomy.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It was found that patients who have intraabdominal infection have significantly longer operative time than those in a non-intraabdominal infection group. 28 This is consistent with Chacon et al, who studied the effect of operative duration and infectious complications and mortality in a large population of patients who underwent hepatectomy. 30 It was found that an operative time greater than 3 h significantly increased mortality, with a considerable peak at 8 h. Furthermore, as the 30-day mortality rate increased in accordance with the operative time, it was concluded that operative time is associated with a linear increase of risk of mortality and infectious complications following hepatectomy.…”
Section: Discussionsupporting
confidence: 89%
“…First, with respect to duration of surgery, a prolonged operative time is associated with major morbidity and mortality, as previously reported. 28 , 29 In earlier study, we reported the factors associated with infectious complications in patients who underwent major hepatectomy were reported. It was found that patients who have intraabdominal infection have significantly longer operative time than those in a non-intraabdominal infection group.…”
Section: Discussionmentioning
confidence: 99%
“…Nutritional therapy is fundamental to the treatment of patients with severe infection and can directly affect the prognosis of patients with IAI. A study by Rungsakulkij et al showed that hypoproteinemia before abdominal surgery was associated with an increased risk of postoperative IAI ( 19 ). Moreover, according to a systematic review conducted by Alharbi et al, hypoproteinemia increases the risk of peritonitis in patients undergoing peritoneal dialysis ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intra-abdominal infections vary in severity and prognosis. Preoperative weight loss, obesity, liver cirrhosis, long operation time, low serum albumin (ALB) level, and long drainage tube indwelling time are all independent risk factors for intra-abdominal infection, [13][14][15][16] and in patients with abdominal infection However, there are few reports on the factors affecting the prognosis of intra-abdominal infection and the evaluation value of these factors on the prognosis. This article aims to explore the distribution of pathogenic bacteria in patients with intra-abdominal infection, clarify the independent factors affecting the prognosis of patients with intra-abdominal infection and their prognostic evaluation value, clinically screen patients with poor prognosis and high-risk patients, to implement timely and effective targeted treatment and improve patient prognosis.…”
Section: Introductionmentioning
confidence: 99%